2022
DOI: 10.1088/1755-1315/976/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of shallot plantation in peat-lands applied with three types of botanical pesticides

Abstract: One method of controlling disease that is environmentally friendly is the use of plant-based pesticides also known as botanical pesticides. The use of botanical pesticides has proven to be effective in controlling several species of pests and plant diseases, because they contains active secondary metabolite compounds. These compounds affect pathogenic microorganisms, so it is feared will also affect antagonistic microorganisms. This research will find out the impact of the application of several botanical pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Application of synthetic pesticides and botanical pesticidesbotanical pesticides to microbial biodiversity, species richness, dominance index, and microbial balance index in shallot plantations The application of botanical pesticides had various effects on the diversity index, species richness index, dominance index, and microbial balance index in shallot plants (Table 6 and Table 7). code, t0 = Negative Control (F. oxysporum inoculation), t1 = Positive control (F. oxysporum + Benomyl fungicide), t2 = Jengkol Skin Powder 0, 125 kg/ha + F. oxysporum inoculation, t3 = Jengkol peel powder 0.25 kg/ha + F. oxysporum inoculation, t4 = Jengkol peel powder 0.375 kg/ha + F. oxysporum inoculation Several studies have found that the application of three types of botanical pesticides (kepayang fruit extract, galam leaf, and Chromolaena odorata) has an effect on the diversity of arthropods (Meiyana et al, 2021) and microbes (Salamiah and Aidawati, 2022) in shallot plantations. The maximum diversity index of 2.03 was obtained when botanical pesticides were combined with 1 ml/L kepayang fruit extract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of synthetic pesticides and botanical pesticidesbotanical pesticides to microbial biodiversity, species richness, dominance index, and microbial balance index in shallot plantations The application of botanical pesticides had various effects on the diversity index, species richness index, dominance index, and microbial balance index in shallot plants (Table 6 and Table 7). code, t0 = Negative Control (F. oxysporum inoculation), t1 = Positive control (F. oxysporum + Benomyl fungicide), t2 = Jengkol Skin Powder 0, 125 kg/ha + F. oxysporum inoculation, t3 = Jengkol peel powder 0.25 kg/ha + F. oxysporum inoculation, t4 = Jengkol peel powder 0.375 kg/ha + F. oxysporum inoculation Several studies have found that the application of three types of botanical pesticides (kepayang fruit extract, galam leaf, and Chromolaena odorata) has an effect on the diversity of arthropods (Meiyana et al, 2021) and microbes (Salamiah and Aidawati, 2022) in shallot plantations. The maximum diversity index of 2.03 was obtained when botanical pesticides were combined with 1 ml/L kepayang fruit extract.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, Chromolaena odorata fruit extract and galam leaf extract significantly reduced the population of microbes by 80.44 % and 75.26 %, respectively. Chirinyuh increased the population by 36.60% (Salamiah and Aidawati, 2022). For example, the nicotine from tobacco plant extracts is categorized by WHO as a group Ib toxin, which is very dangerous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gejala visual daun menguning dan cenderung memuntir (twist). Tanaman yang terserang penyakit moler mudah tercabut karena pertumbuhan akarnya terganggu atau bahkan membusuk (Salamiah & Aidawati, 2022). Pada beberapa tanaman bawang merah ada yang tidak menunjukkan adanya gejala serangan penyakit hingga panen tiba.…”
Section: Masa Inkubasiunclassified
“…Jenis OPT yang banyak ditemukan pada pertanaman bawang merah yaitu penyakit moler, akibat dari Fusarium oxysporum, adalah salah satu penyakit yang paling sering terjadi. Berbagai upaya pengendalian terhadap penyakit moler telah dilakukan, misalnya dengan penggunaan pestisida kimia, benlate dengan intensitas serangan penyakit moler masih tinggi yaitu 71.75% (Suryani et al 2021), dengan pestisida nabati kulit jengkol (Salamiah & Rosa, 2022), sedangkan pestisida nabati kirinyuh mampu meningkatkan populasi biodiversitas di rizosfer pertanaman bawang merah di lahan gambut (Salamiah & Aidawati, 2022) .…”
Section: Pendahuluanunclassified